War Victims and the Right to a City From Damascus to Zaatari - Al-Shoubaki, Hind. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book analyzes the role of integrated spatial planning in constructing eco-sustainable urban housing in post-conflict scenarios and investigates two different spaces in an emergency: Zaatari refugee camp in Jordan and Damascus city in Syria. The book presents a new innovative tool that assists in building a successful and sustainable reconstruction after emergencies which corresponds to the planning approach's heterogeneous nature within emergency situations. The same innovative theoretical framework also covers the ramifications of climate change on the urban built environment and reduces its sociological impact on the stricken communities. This book is intended for researchers, academics, students, spatial planners, policy makers, think tank groups, and public entities who are interested in post-disaster reconstruction and the issues of refugee camps.
1. Chapter I The Temporary City -- 2. Chapter II The Urbicide -- 3. Chapter III Spaces in Emergency -- 4. Chapter IV Urban Emergency Integrated Planning [UEIP] -- 5. Chapter V Conclusion & the Future UEIP -- 6. References -- 7. Appendices.
Keywords: Cities and towns-History.; Cultural property; Archaeology; Urban History; Heritage Management; Cultural Heritage